Hubungan Kecerdasan Naturalis dan Sikap Peduli Lingkungan terhadap Pemahaman Materi Ekosistem Siswa Kelas X di MAN 1 Makassar - Zakiyah Nasywa Zainuddin; Riza Sativani Hayati; Rafiah Mahmudah (Mataram University, 2026)
This study aims to determine the relationship between naturalist intelligence and environmental awareness towards the understanding of ecosystem material of grade X students at MAN 1 Makassar. The study used a quantitative approach with a correlational design. The research sample was determined through a purposive sampling technique. Data were collected using a naturalist intelligence questionnaire, an environmental awareness attitude questionnaire, and an ecosystem material understanding test. Data analysis was carried out using correlation tests and multiple regression. The results of the study showed that there was a positive and significant relationship between naturalist intelligence and the understanding of ecosystem material, as well as between environmental awareness and the understanding of ecosystem material. In addition, simultaneously naturalist intelligence and environmental awareness attitudes also had a significant relationship towards students' understanding of ecosystem material. The conclusion of this study shows that increasing naturalist intelligence and environmental awareness attitudes contributed to improving the understanding of ecosystem material of grade X students.